2014
DOI: 10.1371/journal.pone.0092296
|View full text |Cite
|
Sign up to set email alerts
|

Small Changes in Environmental Parameters Lead to Alterations in Antibiotic Resistance, Cell Morphology and Membrane Fatty Acid Composition in Staphylococcus lugdunensis

Abstract: Staphylococcus lugdunensis has emerged as a major cause of community-acquired and nosocomial infections. This bacterium can rapidly adapt to changing environmental conditions to survive and capitalize on opportunities to colonize and infect through wound surfaces. It was proposed that S. lugdunensis would have underlying alterations in metabolic homeostasis to provide the necessary levels of adaptive protection. The aims of this project were to examine the impacts of subtle variations in environmental conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 37 publications
2
54
0
Order By: Relevance
“…Similarly, ppGpp mutant cells of E. coli were considerably longer than WT cells when cultured under starvation conditions (49). It has also been reported that cells of smaller sizes become increasingly resistant to abiotic stresses, including osmotic and oxidative stresses, thus enhancing their ability to survive under harsh environmental conditions (33,36,(68)(69)(70). This may provide an explanation for why dksA and ppGpp 0 mutants fail to grow in HMM, suggesting that E. amylovora might require both ppGpp and DksA to coregulate cell size and resistance to environmental stresses, thus contributing to overall survival (59).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, ppGpp mutant cells of E. coli were considerably longer than WT cells when cultured under starvation conditions (49). It has also been reported that cells of smaller sizes become increasingly resistant to abiotic stresses, including osmotic and oxidative stresses, thus enhancing their ability to survive under harsh environmental conditions (33,36,(68)(69)(70). This may provide an explanation for why dksA and ppGpp 0 mutants fail to grow in HMM, suggesting that E. amylovora might require both ppGpp and DksA to coregulate cell size and resistance to environmental stresses, thus contributing to overall survival (59).…”
Section: Discussionmentioning
confidence: 97%
“…In general, ppGpp directly interacts with the interface of the ␤= and subunits of RNAP to orchestrate fine-tuning of cellular processes through direct inhibition and activation of genes (26)(27)(28), whereas the DksA protein, which binds to the RNAP secondary channel, greatly enhances the effect of ppGpp by modulating the direct interaction between RNAP and ppGpp (18,28). In addition, ppGpp inhibits RNAP binding to 70 -dependent stringent promoters, thus indirectly allowing RNAP to bind to alternative sigma factors, such as RpoN, and promoting the expression of alternative sigma factor-dependent genes (19,29). Importantly, inhibition of 70 binding by ppGpp is transient and reversible, thus enabling rapid and reversible control of stress response genes (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The changes observed in the metabolome and proteome may represent a phenotypic shift that can occur within an existing population of cells without cell division. Such a shift may be indicative, for example, of the formation of small colony variants that have been previously shown to form in response exposures to NaCl, with accompanying reduced metabolism compared to wild‐type bacteria (Crompton et al, ; Onyango et al, ; Proctor et al, ; von Eiff, ). Prior investigations have shown that small colony variants have slower growth rates, reduced production of virulence factors and some are auxotrophic for important compounds such as haemin and menadione (Bui et al, ; Moisan et al, ; Proctor et al, ; von Eiff et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…high osmotic pressure, the properties of the bacterial cell envelope may be altered in a way that contributes to persistence and the development of resistance. [1,2] To identify such phenotypic alterations in the cell envelope of intact bacterial cells, time-of-flight secondary ion mass spectrometry (ToF-SIMS) appears to be a promising method as it is uniquely capable of probing the chemistry in this region. Investigation of bacterial surfaces may also include bacterial biofilms, which are amorphous and dynamic bacterial community structures.…”
Section: Introductionmentioning
confidence: 99%